"Therapeutic" facemasks. (October 2020) - Gupta, Deepak
Abstract: There must be pathophysiological reason why "cold" viruses like SARS-CoV-2 show proclivity to nasal cavity, oral cavity, pharyngeal cavity and upper airways which have lower temperature than core body temperature. Henceforth, facemasks' "therapeutic" role against SARS-CoV-2 must be explored because personal "therapeutic" environments may get created under facemasks due to rebreathing of 95°F "hot" and 80% "humid" exhalations which may constantly mitigate SARS-CoV-2 inside nasal cavity, oral cavity, pharyngeal cavity and upper airways.